Effectiveness of Pilates as a training method for elderly people: A literature review (Research, Society and Development, 2024)
This article aims to review the effectiveness of Pilates as a training method for elderly people, focusing on the importance of improving functionality and quality of life. Aging leads to a decrease in muscle mass and strength, contributing to frailty and loss of independence. The practice of Pilates, developed by Joseph Pilates in the 1920s, appears as an effective approach to mitigate these effects, promoting improvements in posture, muscular strength, flexibility and balance. This narrative literature review used databases such as PubMed, PEDro, SciELO and BVS, considering studies published between 2014 and 2024. The impacts of Pilates on functionality, balance and strength in elderly people were analyzed, highlighting the relevance of its application for preventing falls and maintaining functional independence. Analysis of studies revealed that Pilates is beneficial for muscle strength, flexibility and balance, with results suggesting a significant reduction in the risk of falls. However, the variability in methodologies and the lack of consensus on best practices indicate the need for more research to consolidate its applications and benefits. The conclusions indicate that Pilates represents an effective alternative to promote healthy aging, offering a method of physical exercise that integrates body and mind to improve the quality of life in the elderly.